Presence of Males Within Laying Hens Affects Tonic Immobility Response and Sociality - Ghareeb , Khaled (International Journal of Poultry Science, 2010)
Fear can be a damaging factor, resulting in poor production and impaired animal welfare. Often fear reactions are elicited in situations that are in some way related to predator defense. As males have a guarding role, mixing the sexes might be a way of reducing fear in flocks of laying hens. Tonic Immobility (TI) is anti-predator behaviours shown by poultry and has been used in behavioural studies to measure the level of fear or stress. A runway test was used in many studies to measure level of sociality in poultry. The effect of males on duration of TI and sociality in female laying hens was studied. ISA Brown and Lohmann Tradition lines were used in each treatment. The treatments were: 1- Female hens and males mixed in a ratio of 1 male to 10 females; 2- All female hens. The presence of males had an effect (p